Breaking the speed-power-accuracy trade-off in current mirror with non-linear CCII feedback. (January 2019) - Julien, Mohan; Bernard, Serge; Soulier, Fabien; Kerzèrho, Vincent; Cathèbras, Guy
Abstract: Design of analog integrated circuit is a matter of trade-offs. Elementary blocks as simple as current mirrors must balance power, speed and accuracy as soon as they have to face dynamic inputs. In this paper, we propose a new structure of high-performance current mirror that overcomes the classical speed-power-accuracy limits. The structure combines a precise cascode current mirror with a custom low-power current conveyor used as a current mode non-linear feedback circuit. It is particularly suitable for fast multipolar current sources with high driving capabilities and small step response time over a large current dynamic. Design method and practical implementation are discussed in details. The circuit realized in AMS CMOS 0.18 μm technology at 1.8 V supply exhibits a large output current dynamic ranging from 160 μA to 2 m A, an average relative current copy error of 0.3% for worst-cases, a maximal settling time of 730 ns for full range step and a maximum quiescent power consumption of 142 μW.